The Impact of Crowd Noise on Officiating in Muay Thai: Achieving External Validity in an Experimental Setting - Myers, Tony D.; Balmer, Nigel J. (Frontiers in Psychology, 2012)
Numerous factors have been proposed to explain the home advantage in sport. Several authors have suggested that a partisan home crowd enhances home advantage and that this is at least in part a consequence of their influence on officiating. However, while experimental studies examining this phenomenon have high levels of internal validity (since only the ‘crowd noise’ intervention is allowed to vary), they suffer from a lack of external validity, with decision-making in a laboratory setting typically bearing little resemblance to decision-making in live sports settings. Conversely, observational and quasi-experimental studies with high levels of external validity suffer from low levels of internal validity as countless factors besides crowd noise vary. The present study provides a unique opportunity to address these criticisms, by conducting a controlled experiment on the impact of crowd noise on officiating in a live tournament setting. Seventeen qualified judges officiated on thirty Thai boxing bouts in a live international tournament setting featuring ‘home’ and ‘away’ boxers. In each bout, judges were randomised into a ‘noise’ (live sound) or ‘no crowd noise’ (noise cancelling headphones and white noise) condition, resulting in 59 judgements in the ‘no crowd noise’ and 61 in the ‘crowd noise’ condition. The results provide the first experimental evidence of the impact of live crowd noise on officials in sport. A cross-classified statistical model indicated that crowd noise had a statistically significant impact, equating to just over half a point per bout (in the context of five round bouts with the ‘ten point must’ scoring system shared with professional boxing). The practical significance of the findings, their implications for officiating and for the future conduct of crowd noise studies are discussed.